KEPEMIMPINAN DALAM SUPERVISI PENDIDIKAN DI MADRASAH - Baharuddin, Baharuddin; Nursita, Lisa (Idaarah: Jurnal Manajemen Pendidikan, 2020)
We try to explore the topic of the problem, namely leadership in supervision in madrasahs through the approach of several aspects and scientific points of view from several experts which are then summarized to find a common thread from each of the aspects found. We found that leadership is a technique or authority that is able to move other people both individually and in groups to carry out activities in achieving organizational goals. In madrasah institutions, educational supervision leadership is needed in order to improve the quality of learning. The duties of education supervisors include helping schools and the government to produce quality graduates, helping teachers develop their profession, helping schools work with parents or the community. Educational supervision leadership acts as a driving force and serves as a central force in improving the quality of learning in madrasah.